2011
DOI: 10.1158/0008-5472.sabcs11-p4-01-18
|View full text |Cite
|
Sign up to set email alerts
|

P4-01-18: AP-1 Blockade Potentiates the Anti-Tumor Effect of Endocrine Treatment and Reverts the Resistant Phenotype in Hormone Receptor-Positive Breast Cancer.

Abstract: Background: Resistance to endocrine therapy is a major clinical issue. The transcription factor AP-1 is a key regulator of cell growth and survival as well as a downstream signaling component of several pathways deregulated in endocrine-resistant breast cancer. We have previously shown that acquired endocrine resistance is associated with increased AP-1 activity. AP-1 has also been shown to interact with and modulate the ER network and transcriptional program, especially under hyperactive growth factor signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Activation of p38 and JNK pathways can lead to increased phosphorylation of ER and/or its important co-activator SRC3 26 , thereby altering ER activity and sensitivity to endocrine agents 34 . Preclinical studies employing genetic strategies have suggested that inhibition of AP-1 transcriptional activity can alter ER activity and circumvent endocrine resistance 28,54 .…”
Section: Underlying Mechanisms Of Altered Er Activity In Endocrine Rementioning
confidence: 99%
See 2 more Smart Citations
“…Activation of p38 and JNK pathways can lead to increased phosphorylation of ER and/or its important co-activator SRC3 26 , thereby altering ER activity and sensitivity to endocrine agents 34 . Preclinical studies employing genetic strategies have suggested that inhibition of AP-1 transcriptional activity can alter ER activity and circumvent endocrine resistance 28,54 .…”
Section: Underlying Mechanisms Of Altered Er Activity In Endocrine Rementioning
confidence: 99%
“…In addition, ER gene products such as cyclin D1 may represent suitable therapeutic targets for improving endocrine sensitivity, as proven by recent results from clinical trials of the CDK4/6 inhibitor palbociclib, in advanced breast cancers 87 . Furthermore, genomic insights into ER reprogramming and its acting regulators, such as AP-1 28,54 and FOXA1 29,63,65 , in endocrine-resistant tumors may not only point to the therapeutic role of these regulators, but also reveal additional key downstream candidate genes for development of predictive biomarkers as well as novel targets to circumvent endocrine resistance.…”
Section: Underlying Mechanisms Of Altered Er Activity In Endocrine Rementioning
confidence: 99%
See 1 more Smart Citation